Linux Shell Scripting Cookbook : over 110 practical recipes to solve real-world shell problems, guaranteed to make you wonder how you ever lived without them /: over 110 practical recipes to solve real-world shell problems, guaranteed to make you wonder how you ever lived without them. (2013) - Unknown
No abstract available